Trade openness and Economic Growth: An empirical analysis from Nigeria - Adekunle, Ahmed Oluwatobi (Ilomata International Journal of Tax and Accounting, 2024)
With a focus on trade openness, interest rates, exchange rates, and foreign direct investment, this study investigates the relationship between trade openness and economic growth in Nigeria between 1986 and 2021. Many observers believe that nations with poor infrastructure are unable to maintain sustained economic growth, particularly when trade openness is hampered by several obstacles. Even though trade liberalization has been extensively studied, few studies thoroughly examine how these factors collectively affect Nigeria's economic growth now, especially over a wide range of data. Using ARDL methodologies, this study shows that trade openness has a significant impact on economic growth, highlighting its critical role in the economy. The study demonstrates that trade openness and foreign direct investment significantly affect economic growth. These revelations improve understanding of the role macroeconomic analysis plays in economic growth and strategic economic management issues.